Update of the population size and breeding performance of gentoo penguins (Pygoscelis papua) at Stranger Point/Cabo Funes, South Shetland Islands - Juares, Mariana Alejandra; Casaux, Ricardo Jorge; Negrete, Javier; Rios, Ayelen; Castillo, Martin; Coria, Néstor Rubén; Santos, Maria Mercedes (Polar Biology)
The plasticity in the trophic ecology, the breeding phenology, and the low nesting site fidelity would be the reasons why most of the gentoo penguin (Pygoscelis papua) populations breeding in the western Antarctic Peninsula and islands of Scotia Arc remained stable or increasing, despite the changing environmental conditions. Regardless of the overall trend, recent studies revealed a decline in the abundance of some gentoo penguin populations at those regions. Therefore, it is highly valuable to update the population size of each colony in order to confirm the current trends of individual colonies and generate a comprehensive overview of the population status. We report the abundance and breeding performance of gentoo penguins at the Stranger Point/Cabo Funes colony from 2000/2001 to 2018/2019. During the last season, 5383 breeding pairs and 5545 chicks in crèche were counted. Despite there were considerable inter-annual fluctuations over the study period, the total number of gentoo penguin breeding pairs increased by 74.6% (+ 3.1% per annum), while the number of chicks crèched increased by 60.0% (+ 2.6% per annum). However, the index of breeding success remained relatively constant over time, varying between 0.74 and 1.23 chicks in crèche/breeding pairs. Gentoo penguins have life-history strategies that are advantageous to face the environmental variability, allowing the species to maintain their breeding performance stable over time and enhance their resilience, which can favour the population growth at Stranger Point. Fil: Juares, Mariana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Casaux, Ricardo Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Centro de Investigación ...